2017
DOI: 10.3390/molecules22101714
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Dipeptidyl Peptidase-IV (DPP-IV) Inhibitory Peptides from Ruditapes philippinarum Hydrolysate

Abstract: Dipeptidyl peptidase-IV (DPP-IV) inhibitory peptides were rapidly identified from Ruditapes philippinarum hydrolysate. The hydrolysate was fractionated by ethanol precipitation and preparative reverse phase high-performance liquid chromatography (RP-HPLC). The fraction which showed the highest DPP-IV inhibitory activity was then analyzed by a high-throughput nano-liquid chromatography electrospray ionization tandem mass spectrometry (nano-LC ESI-MS/MS) method, and the sequences of peptides were identified base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Arg125 (Liu et al, 2017). Simultaneously, the Glu at the N-terminus of ELHQEEPL also formed these three amino acid interactions with F I G U R E 7 (a) and (b) are More 2D graphs for the information of interaction between the ELHQEEPL, HQEEP and DPP-IV residues, respectively DPP-IV.…”
Section: Discussionmentioning
confidence: 92%
“…Arg125 (Liu et al, 2017). Simultaneously, the Glu at the N-terminus of ELHQEEPL also formed these three amino acid interactions with F I G U R E 7 (a) and (b) are More 2D graphs for the information of interaction between the ELHQEEPL, HQEEP and DPP-IV residues, respectively DPP-IV.…”
Section: Discussionmentioning
confidence: 92%
“…As listed in Table 1, the peptide sequences of the F3-8 and F3-11 were Glu-Leu-Lys-Asp-Leu-Lys-Gly-Tyr (ELKDLKGY) and Ile-Leu-Asp-Lys-Val-Gly-Ile-Asn-Tyr (ILDKVGINY), respectively. Figure 4A showed the LC-MS/MS spectrum of single-charged ion with m/z 483.26996, which matched to sequence ELKDLKGY corresponding to bovine α-lactalbumin f (30)(31)(32)(33)(34)(35)(36)(37). Figure 4B showed the LC-MS/MS spectrum of single-charged ion with m/z 517.79901, which matched to sequence ILDKVGINY corresponding to bovine α-lactalbumin f (114-122).…”
Section: Identification Of Dpp-iv Inhibitory Peptidesmentioning
confidence: 94%
“…DPP-IV is a metabolic enzyme that selectively converts the incretin hormones, gastric inhibitory peptide and glucagon-like peptide-1, into their inactive forms, thereby largely influencing postprandial insulin release. Because of its detrimental activity towards postprandial glucose regulation, DPP-IV inhibitory drugs called gliptins have been developed as a therapeutic strategy for type 2 diabetes mellitus (Liu et al, 2017). DPP-IV contains a hydrophobic site S1 with Tyr631, Val656, Trp659, Tyr666 and Val711 residues, and a charged site S2 with Arg125, Glu205, Glu206, Phe357, Ser209 and Arg358 residues (Power et al, 2014).…”
Section: Dipeptidyl Peptidase-iv Inhibitionmentioning
confidence: 99%
“…DPP-IV contains a hydrophobic site S1 with Tyr631, Val656, Trp659, Tyr666 and Val711 residues, and a charged site S2 with Arg125, Glu205, Glu206, Phe357, Ser209 and Arg358 residues (Power et al, 2014). Several studies using bioinformatics, in vitro and animal models have demonstrated that food proteins contain DPP-IV inhibiting peptides within their primary structures (Liu et al, 2017;Udenigwe et al, 2013). These peptides can be released using methods such as enzymatic hydrolysis and fermentation.…”
Section: Dipeptidyl Peptidase-iv Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation